Evaluation of repeated biodisinfestation using Brassica carinata pellets to control Meloidogyne incognita in protected pepper crops - Guerrero-Díaz, M. M.; Lacasa-Martínez, C. M.; Hernández-Piñera, A.; Martínez-Alarcón, V.; Lacasa-Plasencia, A. (Spanish Journal of Agricultural Research, 2013)
The nematode Meloidogyne incognita is responsible for substantial losses in greenhouse-grown peppers in south-eastern Spain. This study evaluates the use of biodisinfestation (BS) (organic amendment + solarisation) as an alternative to using methyl bromide (MB) over three consecutive years to control the nematode in greenhouse conditions. Brassica carinata (BP) pellets or B. carinata (BP) + fresh sheep manure (M) were evaluated in treatments which began on two different dates (August and October) and the results were compared with MB-disinfested and untreated controls. During the third year, the gall index for BP was lower than that obtained for BP+M and in the August treatment than in the October treatment. The commercial crop of pepper fruit obtained with the biodisinfestation treatments begun in August was similar to or higher than that obtained with MB, and higher than that obtained with both October biodisinfestation treatments. The yield of the October biodisinfestation treatments was higher than that of the untreated one. In August of all the years studied, the accumulated exposure times were greater than the thresholds required to kill M. incognita populations at 15 cm depth. The incidence of the nematode did not correspond to the reduction achieved during solarisation, and seemed to increase during the crop cycle. Further studies should look at why high temperatures do not produce a sustained reduction in the populations of Meloidogyne incognita.